Improving anti thrombogenicity of nanofibrous polycaprolactone through surface modification. (September 2019) - Razmjooee, Kavoos; Saber-Samandari, Saeed; Keshvari, Hamid; Ahmadi, Sara
To improve anti thrombogenicity of polycaprolactone, nanofibrous mat of this synthetic polymer is prepared by electrospinning method. Subsequently, plain electrospun nanofibrous polycaprolactone was treated by RF oxygen plasma to initiate the graft copolymerization with acrylamide monomers. The surface morphology and average fiber diameter of plain electrospun nanofibrous polycaprolactone were determined by scanning electron microscopy technique. The chemical composition and surface characteristics of the samples were examined by static contact angle measurements, and attenuated total reflectance Fourier transfer infrared (ATR-FTIR) spectroscopy. Atomic force microscopy was employed to investigate the effect of plasma treatment and graft copolymerization on the surface roughness and topography of the samples. Mechanical properties were measured from the stress–strain curve. The amount of platelet adhesion was observed by scanning electron microscopy images. Results indicate that the polycaprolactone synthetic polymer was successfully electrospun with a nanofibrous micro structure. The ATR-FTIR spectrum confirmed the influence of RF oxygen plasma treatment and graft copolymerization. Contact angle outcomes exhibited a massive improvement in the hydrophilic property of the polycaprolactone-plasma-acrylamide sample, and the surface roughness of this sample also decreased dramatically as atomic force microscopy results showed. The mechanical property of the polycaprolactone-plasma-acrylamide sample shows a negligible reduction in comparison with plain electrospun polycaprolactone. The polycaprolactone-plasma-acrylamide sample possesses proper values of mechanical properties compared to natural blood vessels. The SEM images of polycaprolactone, polycaprolactone-plasma, and polycaprolactone-plasma-acrylamide revealed no adhesion of natural platelets for polycaprolactone-plasma-acrylamide. Thus, the polycaprolactone-plasma-acrylamide vascular prosthesis is fabricated and post processed with sufficient surface properties and anti thrombogenicity.